Предмет: Математика,
автор: BlaZZe
Докажите тождество (tg)^2 a-(sin)^2 a=(sin)^2 a (tg)^2 a
Ответы
Автор ответа:
0
tg²a- sin²a = sin²a * tg²a
sin²a/cos²a - sin²a = sin²a * tg²a
sin²a*(1/cos²a -1) = sin²a * tg²a
sin²a*((1-cos²a)/cos²a) =sin²a*tg²a
sin²a *(sin²a/cos²a) = sin²a * tg²a
sin²a * tg²a = sin²a * tg²a
sin²a/cos²a - sin²a = sin²a * tg²a
sin²a*(1/cos²a -1) = sin²a * tg²a
sin²a*((1-cos²a)/cos²a) =sin²a*tg²a
sin²a *(sin²a/cos²a) = sin²a * tg²a
sin²a * tg²a = sin²a * tg²a
Похожие вопросы
Предмет: Физика,
автор: BoI7poC
Предмет: Математика,
автор: victor7348
Предмет: Математика,
автор: andre1kaa
Предмет: Алгебра,
автор: katofan
Предмет: Химия,
автор: romahusainov45